Research Regarding the Evolution of Agrotourism in Several European Representative Destinations - Ramona Ciolac; Ioan Csosz; Ioan Petroman; Cornelia Petroman; Tiberiu Iancu; Tabita Hurmuzache; Ana Mariana Dincu; Diana Marin (Scientific Papers Animal Science and Biotechnologies, 2023)
The popularity of rural areas, as a possibility to spend the vacation has increased in recent years, in most countries. Changes in attitudes were parallel with changes in European styles to taking the holidays, but also in preferences to return to nature, and various local products. At the European level there is a large interest for the development of agrotourism and its ability to contribute to the development of rural areas, therefore there are countries that have made from agrotourism a lifestyle and additional incomes with witch that pride. Based on this statement this paper follows agrotourism activity in several European countries, considered most representative: Austria, Germany, Switzerland, Italy.